Chitosan-coated poly(lactic-co-glycolic acid) perfluorooctyl bromide nanoparticles for cell labeling in 19F magnetic resonance imaging. (20th January 2016) - Vu-Quang, Hieu; Vinding, Mads Sloth; Xia, Dan; Nielsen, Thomas; Ullisch, Marcus Görge; Dong, MingDong; Nielsen, Niels Chr.; Kjems, Jørgen
Highlights: We aim to make an efficient cell labeling agent for 19 F-MRI. 19 F-MRI is an advantageous imaging technique to obtain the images with background free. By adjusting the weight ratio between chitosan and nanoparticle, we could achieve the best cell labeling efficiency. Cell after labeling could be monitored using 19 F-MRI. Abstract: Noninvasive therapeutic cell tracking methods in living animals are important for understanding cell function and fate in connection with cell therapy. Here we report a new particle system based on chitosan-coated poly(lactic-co-glycolic acid) perfluorooctyl bromide (PLGA PFOB) nanoparticles designed for 19 F magnetic resonance imaging (MRI) cell tracking. Chitosan was adsorbed onto the PLGA PFOB nanoparticles through electric interactions, which led to an increase in the hydrodynamic size and a surface charge proportional to the coating weight ratio. Confocal laser scanning microscopy, flow cytometry analysis and 19 F-MRI showed that to achieve the highest labeling efficiency in vitro, the optimal weight ratio of chitosan to the PLGA PFOB nanoparticles was 1:10 for human mesenchymal stem cells (hMSCs) and 1:100 for Raw 264.7 macrophages. In vivo 19 F-MRI showed that 19 F labeled hMSCs remained at the injected site 24 h after injection. Thus, this study validates that chitosan-coated PLGA PFOB nanoparticles have the potential to track cell migration in vivo .